The Influence of Religiosity and Honesty on Students’ Ghosob Behavior at Bina Umat Islamic Boarding School Yogyakarta - Fanani Murti, Akhmad; Akif Khilmiyah; Abdus Salam Muharam (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study examines the influence of religiosity and honesty on ghosob behavior in students at the Bina Umat Islamic Boarding School in Yogyakarta. Using a quantitative approach, data were collected via a Likert-scale questionnaire from 100 male students aged 15–18 years. Religiosity is measured using Glock & Stark's five dimensions (ideological, ritualistic, experiential, intellectual, and consequential), while honesty is assessed across three domains (toward oneself, others, and God). Multiple linear regression analysis showed that both religiosity (β = 0.239, p < 0.001) and honesty (β = 0.699, p < 0.001) significantly influenced ghosob behavior, with a combined contribution of 76.5% (Adj. R² = 0.765). Honesty was the dominant predictor, accounting for 73.6% of the variance, compared with religiosity (49.8%). The findings show that despite high religiosity, ghosob behavior still occurs because it is normalized in the pesantren culture. The results of the study support Glock & Stark's theory of religiosity, Kohlberg's theory of moral development, and Bandura's theory of social learning, while emphasizing the importance of internalizing the value of honesty as a practical expression of religiosity in character education in the pesantren environment. Keywords: religiosity, honesty, ghosob behavior, pesantren, character education, psychology of Islamic education